PELATIHAN BAHASA INGGRIS DAN PENDIDIKAN AGAMA ISLAM MENGGUNAKAN METODE TPR (TOTAL PHYSICAL RESPONSE) KEPADA ANAK BERKEBUTUHAN KHUSUS - Daryono; Anandha; Dini Anggraheni (Jurnal CULTURE (Culture, Language, and Literature Review), 2019)
The aim of this study is to develop disabled students’s foreign language and religion especially skill and knowledge. Being a language and religion teaching method that uses movement/physical activity to teach several materials (colours, family and asmaul husna), TPR responds favorably to disabled students’s need to be physically active, to learn by doing, and to learn language and religion in meaningful communicative and religion contexts. The activities are classified in relation to function so they can have in a lesson (colour and family) for English and Asmaul Husna for religion in fun ways. This study concludes that the main potentian of using TPR activities in language and religion teaching are in creating conditions similar to first language learning, reducing stress with singing the Asmaul Husna, and in assisting through motor movement. Keywords: Disabled students, TPR (Total Physical Response), language activities, religion activities, motor skills.